Clinical Effectiveness of Benzoyl Peroxide and Clindamycin Combination Therapy in the Treatment of Papulopustular Acne: Combination Therapy for Papulopustular Acne - Niazi, Saira; Gillani, Aneela; Hingoro, Majid Ali; Majeed, Sadia; Anum, Sommiya; Perveen, Zahida (Pakistan Journal of Health Sciences, 2024)
Acne is a prevalent inflammatory skin condition affecting 9% of the global population. Its impact on quality of life and self-esteem leads to depression and anxiety. Combination regimen may be effective in treating acne. Objective: To assess the clinical effectiveness of a fixed-dose combination of 1% clindamycin and 5% benzoyl peroxide in the treatment of mild to moderate papulopustular acne. Methods: An observational prospective study was conducted from June 2023 to December 2023 in the dermatology department of Niazi Welfare Foundation Teaching Hospital, Sargodha. 72 patients with mild to moderate papulopustular acne were monitored. A gel containing a combination of 1% clindamycin and 5% benzoyl peroxide was applied once daily for 12 weeks. Descriptive statistics was used for demographic variables. Chi-square test was used to evaluate the treatment effects at a significance level, p-value<0.05. Adverse effects related to therapy were shown as bar chart. Results: Findings of the study showed that during therapy in the period between the 3rd and 6th weeks, the proportion of patients who achieved excellent improvement increased by 25% from 40/72 (55.5%) to 57/72 (79.1%) respectively p < 0.05. Conclusions: The study concluded that the combination of 1% clindamycin and 5% benzoyl peroxide was effective in treating mild to moderate papulopustular acne.